HUBUNGAN KONFORMITAS TEMAN SEBAYA DENGAN PERILAKU IMPULSIVE BUYING PADA SISWA REMAJA SEKOLAH MENENGAH ATAS (SMA) NEGERI X PRINGSEWU - Widi Putri, Rahmadilla (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
The purpose of this study was to determine how impulsive buying behavior and peer conformity are related to each other among high school students at State Senior High School 2 Pringsewu. This study used correlational techniques and quantitative methodology. A total of 222 respondents in grades XI and XII were selected using cluster random sampling techniques. The impulsive purchasing scale based on Rook & Fisher's theory (1987) and the conformity scale based on Baron and Byrne's theory (2005) were used as data collection tools. The Spearman correlation test was used to analyze the data after the normality and linearity tests indicated that the data were not normally distributed or linear. According to the test results, there is a substantial and positive correlation between impulsive purchasing behavior and peer conformity, with a correlation coefficient of 0.294 and a significance level of 0.000 (p < 0.05). This implies that students' impulsive purchasing behavior increases with peer conformity.